WORK SATISFACTION MEDIATION ON THE EFFECTS OF ORGANIZATIONAL SUPPORT TOWARDS ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Khoridatun Nisa; Susi Widjajani; Budiyanto Budiyanto (Universitas muhammadiyah malang, 2019)
Organizational citizenship behavior can be influenced by many factors, including perception of organizational support and job satisfaction. Perception of organizational support and job satisfaction are two things that are interrelated and can affect organizational citizenship behavior. This study aims to examine the effect of organizational support perception on organizational citizenship behavior, perception of organizational support for job satisfaction, job satisfaction on organizational citizenship behavior, as well as the influence of perception of organizational support for organizational citizenship behavior through job satisfaction as a mediating variable. The population in this study were employees of regional companies in Kebumen Regency. The sample of this study was taken using a purposive sampling technique with the criteria of employees who had a minimum work period of 1 year and had senior high school/ equivalent education at least 99. The data collection used a questionnaire with alternative answers options using the Likert scale method, each of which had already been tested and met the validity and reliability requirements. This study tested the hypothesis using regression analysis. The results of data analysis show that there is a positive and significant influence of perception of organizational support towards organizational citizenship behavior; perception of organizational support towards job satisfaction; job satisfaction towards organizational citizenship behavior; and perception of organizational support towards organizational citizenship behavior through job satisfaction as the mediating variables.